Vprašanje umetnostnega naročništva pri treh dolnjeprekmurskih župnikih, ki so v poznem 17. stoletju študirali v Bologni - Žnidaršič Golec, Lilijana (Acta historiae artis Slovenica, 2023)
The contribution presents the question of the art patronage of three priests who studied theology in Bologna in the 1680s and later served in various parishes in the lower Prekmurje region. Nikolaj Kiš, Emerik Nyilas and Peter Pau-lušič were all priests of the Zagreb diocese and recorded as leading the parishes of Dobrovnik, Turnišče, and Dolnja Lendava (today Lendava) for longer or shorter periods. In the biographical sketches that the article provides for each of them, significant attention is paid to their stay at the Illyrian-Hungarian College in Bologna or their studies at the university there, their academic, social, and other connections, and the traces they left or could have left in the field of art. One of the most important goals of the contribution is to stimulate further research on the influences and transmission of artistic and cultural examples from Bologna (and Italy) to the lower Prekmurje region and other parts of the Zagreb and neighbouring dioceses.
Keywords: art commission; duhovniki; Ilirsko-ogrski kolegij v Bolonji; Illyrian-Hungarian College in Bologna; Prekmurje (Slovenia); priests; umetnostno naročništvo